2018
DOI: 10.4172/pharmaceutical-sciences.1000351
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Antimicrobial Activity of Fluorine Containing Pyrazole-clubbed Dihydropyrimidinones

Abstract: Desai, et al.: Fluorine Containing Pyrazole-clubbed DihydropyrimidinonesIn the present communication synthesis of pyrazole-containing dihydropyrimidinone motifs (4a-o) and their antimicrobial activity and cytotoxicity were reported. The newly synthesized compounds were characterized using infrared, proton nuclear magnetic resonance, carbon-13 nuclear magnetic resonance and mass spectral techniques. Compounds 4b, 4c, 4f, 4g, 4i and 4j were the most active derivatives identified during antimicrobial activity scr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 37 publications
(38 reference statements)
0
7
0
Order By: Relevance
“…This revealed the influence of electron-withdrawing functional groups on antimicrobial activity. This type of compound with an electron-withdrawing group has been reported to have excellent antimicrobial activity [ 57 ]. Against P. aeruginosa , Q8 having chlorine as its substituent, showed excellent activity higher than the reference standards while Q7 has the same MIC value of 0.2 µg/mL as ciprofloxacin.…”
Section: Resultsmentioning
confidence: 99%
“…This revealed the influence of electron-withdrawing functional groups on antimicrobial activity. This type of compound with an electron-withdrawing group has been reported to have excellent antimicrobial activity [ 57 ]. Against P. aeruginosa , Q8 having chlorine as its substituent, showed excellent activity higher than the reference standards while Q7 has the same MIC value of 0.2 µg/mL as ciprofloxacin.…”
Section: Resultsmentioning
confidence: 99%
“…Pyridine heterocycle was confirmed through C N stretching at 1609 cm À1 . 1 H NMR signal presented at 7.00 ppm confirmed the presence of C H (arylidene proton). Furthermore, the signal that appeared at 1.85 ppm confirmed three protons presented in the methyl group of the thiazolidinone core structure.…”
Section: Introductionmentioning
confidence: 82%
“…To adequately handle the spread of antimicrobial resistance, the search for the advancement of novel antimicrobial agents is the only way to resolve the problem. Heterocyclic compounds have drawn the attention of scientific experts and pharmacologists in light of their biological significance [1,2]. It has been observed that hybrids of bioactive pharmacophores (pyridine, coumarin, and 4-thiazolidinone) in the current medications create a significant effect on the pharmaceutical profile [3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Thioxoimidazolidin-4-one derivatives prevent the α-amylase and α-glucosidase enzymes activities and used for the treatment of diabetes-related diseases 7 . Moxonidine is a new generation antihypertensive drug containing imidazole moiety 8 . Tipifarnib is an imidazole derivative which used for treatment of acute myeloid leukemia (AML) 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Moxonidine is a new generation antihypertensive drug containing imidazole moiety 8 . Tipifarnib is an imidazole derivative which used for treatment of acute myeloid leukemia (AML) 8 . Thiohydantoins, is well known due their amazing applications as human immunodefi ciency virus (HIV) 9, 10 , antimutagenic 12,13 , anticarcinogenic 14 , anti-microbial 15-17 , anti-viral 18 , hypolipidemic 19,20 , anti-thyroidal 21- 23 and tuberculosis 24 , anti-ulcer, anti-infl ammatory agents 25 , and pesticides 26 .…”
Section: Introductionmentioning
confidence: 99%